Analysis of castor bean ribosome-inactivating proteins and their gene expression during seed development - Loss-Morais, Guilherme (Sociedade Brasileira de Genética, 2013)
Ribosome-inactivating proteins (RIPs) are enzymes that inhibit protein synthesis after depurination of a specific adenine in rRNA. The RIP family members are classified as type I RIPs that contain an RNA-N-glycosidase domain and type II RIPs that contain a lectin domain (B chain) in addition to the glycosidase domain (A chain). In this work, we identified 30 new plant RIPs and characterized 18 Ricinus communis RIPs. Phylogenetic and functional divergence analyses indicated that the emergence of type I and II RIPs probably occurred before the monocot/eudicot split. We also report the expression profiles of 18 castor bean genes, including those for ricin and agglutinin, in five seed stages as assessed by quantitative PCR. Ricin and agglutinin were the most expressed RIPs in developing seeds although eight other RIPs were also expressed. All of the RIP genes were most highly expressed in the stages in which the endosperm was fully expanded. Although the reason for the large expansion of RIP genes in castor beans remains to be established, the differential expression patterns of the type I and type II members reinforce the existence of biological functions other than defense against predators and herbivory.